The boundary-crossing constraint revisited: movement verbs across varieties of Spanish - Calle Bocanegra Rosalía (Cognitive Linguistics)
Talmy divided the world’s languages according to how they express movement. Spanish, a verb-framed language, purportedly constrains the use of motion verbs expressing the manner of movement (such as roll) to contexts in which no spatial boundary is crossed. Previous research suggests that this constraint sometimes does not apply. We report the first large-scale investigation of the constraint and its modulating factors (movement direction, verb type, entering/exiting, Ground size, the preposition used) across different Spanish-speaking communities. A task with open-ended description of animated videos, a sentence interpretation task, and a rating task found that Spanish and Latin American speakers (n = 180 in total) often use manner verbs to describe boundary-crossing situations (especially entering a place), although this is modulated by the preposition following the verb (more with a than en). Better understanding of this constraint in verb-framed languages has applications in, for instance, L2 acquisition research.